The Christmas star [videorecording (DVD)] - Shapiro, Alan, 1957-; Dysinger, Carol; Asner, Edward; Auberjonois, René, 1940-2019; Gwynne, Fred; Metzler, Jim, 1955-; Tyrrell, Susan, 1945-2012 (Disney DVD., 2004)
A counterfeiter escapes prison through his extraordinary likeness to St. Nick. Christmas is near, and with the police closing in, he is unable to recover loot from an earlier caper without taking advantage of two neighborhood kids who believe he is Santa.